Klotho and smoking – An interplay influencing the skeletal muscle function deficits that occur in COPD. (April 2016) - Patel, M.S.; Donaldson, A.V.; Lewis, A.; Natanek, S.A.; Lee, J.Y.; Andersson, Y.M.; Haji, G.; Jackson, S.G.; Bolognese, B.J.; Foley, J.P.; Podolin, P.L.; Bruijnzeel, P.L.B.; et al.
Abstract: Background: Klotho is an 'anti-ageing' hormone and transmembrane protein; Klotho deficient mice develop a similar ageing phenotype to smokers including emphysema and muscle wasting. The objective of this study was to evaluate skeletal muscle and circulating Klotho protein in smokers and COPD patients and to relate Klotho levels to relevant skeletal muscle parameters. We sought to validate our findings by undertaking complimentary murine studies. Methods: Fat free mass, quadriceps strength and spirometry were measured in 87 participants (61 COPD, 13 'healthy smokers' and 13 never smoking controls) in whom serum and quadriceps Klotho protein levels were also measured. Immunohistochemistry was performed to demonstrate the location of Klotho protein in human skeletal muscle and in mouse skeletal muscle in which regeneration was occurring following injury induced by electroporation. In a separate study, gastrocnemius Klotho protein was measured in mice exposed to 77 weeks of smoke or sham air. Results: Quadriceps Klotho levels were lower in those currently smoking (p = 0.01), irrespective of spirometry, but were not lower in patients with COPD. A regression analysis identified current smoking status as the only independent variable associated with human quadriceps Klotho levels, an observation supported by the finding that smoke exposed mice had lower gastrocnemius Klotho levels than sham exposed mice (p = 0.005). Quadriceps Klotho levels related to local oxidative stress but were paradoxically higher in patients with established muscle wasting or weakness; the unexpected relationship with low fat free mass was the only independent association. Within locomotor muscle, Klotho localized to the plasma membrane and to centralized nuclei in humans and in mice with induced muscle damage. Serum Klotho had an independent association with quadriceps strength but did not relate to quadriceps Klotho levels or to spirometric parameters. Conclusions: Klotho is expressed in skeletal muscle and levels are reduced by smoking. Despite this, quadriceps Klotho protein expression in those with established disease appears complex as levels were paradoxically elevated in COPD patients with established muscle wasting. Whilst serum Klotho levels were not reduced in smokers or COPD patients and were not associated with quadriceps Klotho protein, they did relate to quadriceps strength. Highlights: Klotho is expressed in skeletal muscle where levels are reduced by smoking. In COPD, quadriceps Klotho levels are paradoxically raised in patients with wasting. Klotho may have a role in the process of skeletal muscle regeneration. Systemic Klotho levels are associated with quadriceps strength. Smoking may mediate skeletal muscle dysfunction by influencing Klotho expression.